Inflammation and Cardiovascular Diseases in the Elderly: The Role of Epicardial Adipose Tissue - Conte, Maddalena; Petraglia, Laura; Poggio, Paolo; Valerio, Vincenza; Cabaro, Serena; Campana, Pasquale; Comentale, Giuseppe; Attena, Emilio; Russo, Vincenzo; Pilato, Emanuele; Formisano, Pietro; Leosco, Dario; et al. (Frontiers in Medicine, 2022)
Human aging is a complex phenomenon characterized by a wide spectrum of biological changes which impact on behavioural and social aspects. Age-related changes are accompanied by a decline in biological function and increased vulnerability leading to frailty, thereby advanced age is identified among the major risk factors of the main chronic human diseases. Aging is characterized by a state of chronic low-grade inflammation, also referred as inflammaging. It recognizes a multifactorial pathogenesis with a prominent role of the innate immune system activation, resulting in tissue degeneration and contributing to adverse outcomes. It is widely recognized that inflammation plays a central role in the development and progression of numerous chronic and cardiovascular diseases. In particular, low-grade inflammation, through an increased risk of atherosclerosis and insulin resistance, promote cardiovascular diseases in the elderly. Low-grade inflammation is also promoted by visceral adiposity, whose accumulation is paralleled by an increased inflammatory status. Aging is associated to increase in epicardial adipose tissue (EAT), the visceral fat depot of the heart. Structural and functional changes in EAT have been shown to be associated with several heart diseases, including coronary artery disease, aortic stenosis, atrial fibrillation, and heart failure. EAT increase is associated with a greater production and secretion of pro-inflammatory mediators and neuro-hormones, so that thickened EAT can pathologically influence, in a paracrine and vasocrine manner, the structure and function of the heart and is associated to a worse cardiovascular outcome. In this review, we will discuss the evidence underlying the interplay between inflammaging, EAT accumulation and cardiovascular diseases. We will examine and discuss the importance of EAT quantification, its characteristics and changes with age and its clinical implication.